Physicochemical Evaluation of Diploknema butyracea Seed Extract and Formulation of Ketoconazole Ointment by Using the Fat as a Base. (16th November 2021) - Pandey, Jitendra; Khanal, Bimal; Bhandari, Jhabilal; Bashyal, Rishav; Pandey, Asmita; Mikrani, Asgar Ali; Aryal, Pramod; Bhandari, Ravin
Abstract : The fat obtained from the ripened seeds of Diploknema butyracea is widely used as a vegetable oil in rural areas of Nepal. This study was aimed for the physicochemical evaluation (acid value, iodine value, saponification value, peroxide value, ester value, pH, and liquefaction point) of the Diploknema butyracea seed extract (chyuri fat) and the formulation of 2% w/w ketoconazole ointment by using it as a base. All the physicochemical parameters were determined quantitatively by using the method of Indian Pharmacopoeia (IP), volume-I. By fusion method, 3 different formulations F-A, F-B, and F-C were prepared, in which different proportions of chyuri fat, polyethylene glycol 6000 (PEG 600), Tween 80, and propylene glycol were used as an ointment base. Various quality parameters such as spreadability, extrudability, viscosity, smoothness, pH, average fill weight, assay, content uniformity, accelerated stability, and drug release profiles were determined. HPLC was used for the determination of ketoconazole content in the ointment formulations. Physicochemical evaluation of the chyuri fat ensured its suitability for industrial purpose. The active ingredient release profile of formulations F-A (87.71%), F-B (88.89%), and F-C (91.09%) after 5 hours were within acceptable range along with other parameters. Assay of the formulations F-A, F-B, and F-C were reported to be 103.01, 107.9, and 102.45%, respectively. Overall, evaluation of the formulation F-A, prepared by using chyrui fat only, gave satisfactory results and most of the parameters were statistically similar (p > 0.05 ) to the F-B and F-C formulated by incorporating a certain proportion of synthetic base. Thus it can be concluded that chyuri fat can be the best alternative to replace the expensive synthetic base.